PENGEMBANGAN INDIKATOR PENILAIAN KINERJA PENERAPAN FAKTOR LINGKUNGAN SUPPLY CHAIN UMKM - Sri Wahjuni Latifah; Dhaniel Syam (Fakultas Ekonomi dan Bisnis, 2020)
This research is conducted with the aim of developing SMES performance assessment indicators by implementing the supply chain environmental factors so that it can be used to assess the performance of SMES not only financial based but to non Financial. Data is collected by sending queitioner and interviews to MSME managers, employees and consumers are obtained sixty SMES. The research variables are developed from the Balance Score Card concept and supply chain management. Data analysis techniques are done with qualitative descriptive. And then the analysis of factors to determine the indicator in the determination of SMES performance. The results showed that there are four factors that can be used to determine the SME performance indicators: resource factors, financial factors, customer factors and the SCM (Supply Chain Management) factor.